Literatura de Cordel: um fazer popular a caminho da sala de aula. - Silva, Josivaldo Custódio da (2007)
This work has the goal of presenting some reading experiences of cordel literature in high school classes. They worked with cordel works of José Costa Leite, Marcelo Soares and Cleydson Monteiro, poets who live in Condado-PE, Timbaúba-PE and Campinas-SP respectively. This proposal is basead uponan educational perspective towards the reading and working with cordel works in the classrooms, evidencing the experience of the poets and students. We pointed out and discussed some methodologies of working with literature, as important elements for the accomplishment of experiences with a popular literature genre. Therefore, it‟s attested that it‟s possible to work the cordel literature in classrooms without losing the funny and creative characteristics of it, creating possibilities for the dialogue with literature e other arts.